Indicating vertical deviation of historical buildings using geodetic methods - case study of brick and wood tower in Nowe Miasteczko = Wyznaczenie wychyleń obiektów zabytkowych z wykorzystaniem metod geodezyjnych na przykładzie wieży o konstrukcji murowano drewnianej w Nowym Miasteczku - Mrówczyńska, Maria; Gibowski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the possibilities of applying geodetic methods to determine the vertical deviation of historical buildings. In particular, the results of measurements obtained for a brick and wood Town Hall Tower located in the town of Nowe Miasteczko have been presented. Geodetic measurements of vertical deviation taken before and after carrying out repairs which were aimed at stopping or eliminating the destructive processes of degradation taking place, especially in the wooden part of the tower. During the renovation works, attention was also given to improving the technical condition of the building, which was reflected by the results of the measurements and calculations.
Keywords: zabytki architektury; wieża ratusza; wychylenie od pionu; pomiary geodezyjne; historic building; city hall tower; vertical deviation; geodetic measurements